Locating Malangatana: decolonisation, aesthetics and the roles of an artist in a changing society - De Andrade Pissarra, Mario (Department of Sociology, 2020)
This thesis responds to the dearth of detailed studies of pioneering African modernists; and the need for fresh theoretical frameworks for the interpretation of their art. Building on recent scholarship that applies decolonisation as an epistemic framework, it argues that a productive decolonial discourse needs to consider concurrent forms of nationalism and cultural agency in both the anti/colonial and postcolonial periods. Central to this approach is an analysis of the aesthetic responses of artists to the experiences and legacies of colonialism. This thesis is grounded in a study of Malangatana Valente Ngwenya (1936-2011), Mozambique’s most celebrated artist. It draws substantially on archival material and rare publications, mostly in Portuguese. The artist’s career is located within changing social and political contexts, specifically the anti/colonial period, and the promise and collapse of the postcolonial revolutionary project, with the pervasive influence of the Cold War highlighted. Following the advent of globalisation, the artist’s role in normalising postcolonial relations with Portugal is foregrounded. Parallel to his contribution to Mozambican art and society, Malangatana features prominently in surveys of modern African art. The notion of the artist fulfilling divergent social roles at different points in time for evolving publics is linked to an analysis of his emergence as a composite cultural sign: autodidact; revolutionary; cultural ‘ambassador’; and global citizen. The artist’s decolonial aesthetics are positioned in relation to those of his pan-African peers, with four 6 themes elaborated: colonial assimilation; anti-colonial resistance; postcolonial dystopia; and the articulation of a new Mozambican identity. Key to this analysis is an elaboration of the concept of the polemic sign, initially proposed by Jean Duvignaud (1967), adapted here to interpret the artist’s predilection for composite visual signs that, in their ambivalence and often provocative significations, resist processes of definitive translation. It is argued that through a juxtaposition of disparate forms of signs, and the simultaneous deployment of semi-realist and narrative pictorial strategies, the artist develops a complex, eclectic and evocative aesthetic that requires critical and open-ended engagement. The thesis concludes with provocative questions regarding the extent to which the artist’s aesthetics reflect hegemonic national narratives, or act to unsettle these. of a new Mozambican identity. Key to this analysis is an elaboration of the concept of the polemic sign, initially proposed by Jean Duvignaud (1967), adapted here to interpret the artist’s predilection for composite visual signs that, in their ambivalence and often provocative significations, resist processes of definitive translation. It is argued that through a juxtaposition of disparate forms of signs, and the simultaneous deployment of semi-realist and narrative pictorial strategies, the artist develops a complex, eclectic and evocative aesthetic that requires critical and open-ended engagement. The thesis concludes with provocative questions regarding the extent to which the artist’s aesthetics reflect hegemonic national narratives, or act to unsettle these.